The Legal Standing And Validity Of Smart Contracts as Assessed Under The Requirements of a Valid Contract in Indonesian Civil Law - Chandera Halim (Civiliza Publishing, 2026)
This research examines the legal standing and validity of smart contracts under the requirements of a valid contract in Indonesian civil law, particularly within the framework of Article 1320 of the Indonesian Civil Code (Burgerlijk Wetboek), which requires consent, legal capacity, a specific object, and a lawful cause. Using normative juridical research with statutory and conceptual approaches, the study analyzes civil law provisions, regulations on electronic information and transactions, and doctrinal perspectives on digital contract law. The findings indicate that smart contracts can, in principle, fulfill the elements of a valid contract, especially regarding consent and object, as long as the parties’ intentions are identifiable and the contractual terms are sufficiently clear despite being expressed in code. However, challenges remain in assessing legal capacity, ensuring genuine consent, and determining lawful cause, particularly when execution occurs autonomously without direct human involvement. Therefore, although Indonesian civil law allows their recognition, clearer legal interpretation and regulatory development are necessary to ensure legal certainty and protection of the parties.